Overcoming Rotary Mechanism Limitations in CNC Machines: A 3-PRS Approach - Madaj, Rudolf; Veres, Matus; Kohar, Robert; Weis, Peter; Sulek, Filip (Manufacturing Technology Journal, 2025)
This paper presents the design and analysis of a 3-PRS mechanism for positioning cutting heads in CNC machines, addressing limitations of traditional rotary mechanisms such as hose twisting, wear, and limited modularity. Kinematic and dynamic analyses guided actuator selection and confirmed bearing durability. The mechanism achieves a favourable load-to-weight ratio and integrated Z-axis movement, making it suitable for simpler gantry CNC machines. Though programming is complex due to multiaxis synchronization, the modular design supports easy adaptation to different tools. Future research will focus on reducing the eccentric torch offset and refining dimensions to enhance versatility. The mechanism has strong potential in sectors like automotive, aerospace, and construction.
Keywords: Dynamic analysis; Engineering design; Kinematic analysis; Modular design; 3-PRS mechanism